A study on the key factors for effective e-learning - Pathan, Al-Sakib Khan; Islam, Humayun Kadir (Medwell Publishing, 2005)
In the recent era of Computer and Internet technologies e-learning has become a major issue. E-learning works, to some extent, everywhere. By now, it has been embraced by the government, corporate and academic institutions throughout the world. With the advancement of technology, e-learning has become a reality but several questions are still unanswered. It is a big question how to make it more effective. The intent of this paper is to analyze the key factors of elearning and finding out the ways to use the key factors for successful and effective elearning.